Assessment of polylactide as optical material - Matthias Balthasar Kesting; Jörg Meyer; Gunnar Seide (Optical Materials: X)
Due to growing concerns considering environmental pollution, interest in bioplastics is rising. For technical applications, the respective materials have to meet high requirements. In optical applications these include transmittance, refractive index and dispersion but also dimensional stability, resistance against thermal influences and radiation induced degradation. Polylactide (PLA), a bio-based and biodegradable polymer, is already applied in high tech applications such as bioresorbable implants. The material shows favorable optical properties in its glassy state and excellent resistance against photodegradation. However, the application of PLA is hindered by its crystallization behavior. When exposed to temperatures above 55–60 °C it turns hazy. This might be avoided by hindering crystallization or tailoring crystal morphology. In this critical review, current applications of PLA are discussed and its broad use is shown. A literature search is carried out considering fully bio-based and biodegradable plastics for optical applications. The results show that currently no material is commercially available that meets all requirements set. Finally, an overview of the current state in research is provided, considering PLA-based materials with adapted crystallization behavior under the aspect of transparency. This includes use of additives, formulation of blends and material treatments. Finally, recommendations for the goal of achieving highly sustainable PLA-based optical components are given.